Analisis Epistemologis dan Ontologis terhadap Sistem Pengelolaan Rekam Medis di Rumah Sakit : Literatur Review - Mega Ermasari; Suryo Ediyono (Jurnal Ners, 2026)
This study aims to analyze medical record management systems in hospitals through a philosophy of science approach, particularly from epistemological and ontological perspectives. The method employed is a qualitative approach with a literature review design, examining various reputable scientific articles to identify concepts, patterns, and theoretical frameworks related to medical record systems as knowledge systems. The findings indicate that medical record systems function not only as documentation tools, but also as ontological representations of clinical reality and as epistemological media for the construction of medical knowledge. From an ontological perspective, medical record systems represent complex health realities through standardized data structures, although they often involve a reduction of meaning. Meanwhile, from an epistemological perspective, these systems reflect the processes of constructing and validating medical knowledge, which involve varying degrees of certainty, interpretation, and potential bias. This study concludes that the evaluation of medical record systems requires a comprehensive philosophical approach in order to develop systems that are not only technically efficient, but also epistemologically valid and ontologically representative. Keywords: philosophy of science, epistemology, ontology, medical records, health information systems, hospitals